Organic Acid-Based Natural Deep Eutectic Solvents: A Comparative Study for Chitin Extraction from Crab Shell By-Products - Sunton, Nareerat; Anglong, Chakkapat; Limpawattana, Maruj; Huang, Wen-Can; Mao, Xiangzhao; Klaypradit, Wanwimol (Journal of Fisheries and Environment, 2024)
Conventional chitin extraction using acid/alkali method is effective but involves harsh chemicals. Biological methods offer improved consistency but often result in limited chitin solubility. This study evaluated the efficiency of lactic acid-based and succinic acid-based natural deep eutectic solvents (NADES) for chitin extraction from crab shells. Choline chloride was mixed with either lactic acid (lactic-NADES) or succinic acid (succinic-NADES) and combined with crab shell powder (CS) in a 10:1 ratio. The mixture was then heated using microwaves for varying durations. The results showed that lactic-NADES achieved higher demineralization and deproteinization efficiencies than succinic-NADES. Optimal extraction was achieved with 3 M lactic acid at a CS:lactic-NADES ratio of 1:20, with a microwave irradiation time of 5 min, yielding demineralization and deproteinization efficiencies of 97.78±0.73% and 81.33±0.91%, respectively. The microstructure, crystallographic organization, functional groups, and thermal stability of the optimal extracted chitin were then compared to those of conventionally extracted chitin. Analysis using SEM, FT-IR, XRD, and TGA showed that chitin obtained via the lactic-NADES method had characteristics comparable to those extracted using traditional acid/alkali methods. Thus, the lactic-NADES method presents a promising alternative for chitin extraction, offering similar quality with potentially fewer environmental impacts.